2018
DOI: 10.1016/j.neuro.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-derived neuronal models for in vitro neurotoxicity assessment

Abstract: Neurotoxicity testing still relies on ethically debated, expensive and time consuming in vivo experiments, which are unsuitable for high-throughput toxicity screening. There is thus a clear need for a rapid in vitro screening strategy that is preferably based on human-derived neurons to circumvent interspecies translation. Recent availability of commercially obtainable human induced pluripotent stem cell (hiPSC)-derived neurons and astrocytes holds great promise in assisting the transition from the current sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 34 publications
6
109
0
Order By: Relevance
“…We observed that astrocytes influenced hiPSC‐MN electrophysiology over time with increases in spiking and bursting activity that far exceeded the activity of hiPSC‐MN cultured in the absence of astrocytes. These findings are consistent with previous observations on human iPSC‐derived cortical neurons . Moreover, the spike frequencies we recorded are comparable to those reported by MEA studies with cortical hiPSC‐N or with rodent primary MN .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed that astrocytes influenced hiPSC‐MN electrophysiology over time with increases in spiking and bursting activity that far exceeded the activity of hiPSC‐MN cultured in the absence of astrocytes. These findings are consistent with previous observations on human iPSC‐derived cortical neurons . Moreover, the spike frequencies we recorded are comparable to those reported by MEA studies with cortical hiPSC‐N or with rodent primary MN .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the identity of these cells as iPSC‐MN, in our coculture platform we observed a robust and consistent response to AMPA receptor agonists/antagonists (KA and CNQX, respectively). As shown by others for hiPSC‐cortical neurons , this effect was maturation‐dependent, as it appeared only after 3–4 weeks in vitro, whereas it was absent at earlier stages of maturation. The response to the GABA antagonist bicuculline was less robust, a finding consistent with a lower representation of GABA receptors.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In vitro culture of enriched neuronal populations allows for enhanced study of direct/intrinsic factors under a variety of conditions. Such cultures are commonly derived from either embryonic/neonatal tissues [1][2][3][4][5] or induced pluripotent stem cells (iPSCs) [6][7][8]. Embryonic/neonatal tissues have weak neuronal connections which allow for their isolation and culture without severe injury [9] and are particularly useful for the study of neuronal development [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%